2006
DOI: 10.2106/jbjs.e.00228
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Primarily Ligamentous Lisfranc Joint Injuries: Primary Arthrodesis Compared with Open Reduction and Internal Fixation<sbt aid="1080838">A Prospective, Randomized Study</sbt>

Abstract: A primary stable arthrodesis of the medial two or three rays appears to have a better short and medium-term outcome than open reduction and internal fixation of ligamentous Lisfranc joint injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
341
6
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(373 citation statements)
references
References 13 publications
8
341
6
18
Order By: Relevance
“…Certainly this brings a protocol bias to the positive outcome of increased hardware removal rates in the ORIF group. Even with this built-in removal from Henning, the rates here were similar to those of Ly et al [13] with CIs of 0.07 to 0.62 and 0.10 to 0.59, respectively. Also, three patients in the Henning group refused to undergo hardware removal if they were asymptomatic.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Certainly this brings a protocol bias to the positive outcome of increased hardware removal rates in the ORIF group. Even with this built-in removal from Henning, the rates here were similar to those of Ly et al [13] with CIs of 0.07 to 0.62 and 0.10 to 0.59, respectively. Also, three patients in the Henning group refused to undergo hardware removal if they were asymptomatic.…”
Section: Discussionsupporting
confidence: 86%
“…This protocol bias may have strongly influenced their removal rates. Ly et al [13] had similar removal rates without such a standard protocol. Second, only two of the three studies reported on hardware removal.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This author has treated all Lisfranc injuries with ORIF with primary arthrodesis over the past 10 years and has anecdotally noted a similar experience as Ly and Coetzee [11], with generally consistent pain relief and return to function relative to ORIF alone (Fig. 3a-c).…”
Section: Orif With Primary Arthrodesismentioning
confidence: 86%
“…Initial studies suggested that over 90% of patients were able to return to pre-operative level of activity following primary arthrodesis [11] and that primary arthrodesis significantly reduced the rate of both planned and unplanned secondary surgeries relative to ORIF alone [12]. ORIF with primary arthrodesis also appears to yield good results for combined bony and ligamentous patterns [13].…”
Section: Orif With Primary Arthrodesismentioning
confidence: 99%